2020
DOI: 10.1001/jamapsychiatry.2020.0322
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stressors at Work and the Risk of Sickness Absence Due to a Diagnosed Mental Disorder

Abstract: IMPORTANCE Mental health problems are associated with considerable occupational, medical, social, and economic burdens. Psychosocial stressors at work have been associated with a higher risk of mental disorders, but the risk of sickness absence due to a diagnosed mental disorder, indicating a more severe condition, has never been investigated in a systematic review and meta-analysis. OBJECTIVETo synthesize the evidence of the association of psychosocial stressors at work with sickness absence due to a diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
140
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 63 publications
4
140
0
6
Order By: Relevance
“…Healthcare workers are a particularly vulnerable group due to their higher risk of being infected by SARS-CoV-2 and their working conditions during the height of infections included long work hours, cancelled holidays, adverse physical and psychosocial work conditions, that is, high psychological and emotional demands and low control. 18 19 These working conditions, together with moral distress in relation to the family situation, may increase the risk for mental health problems and sickness absence in this female-dominated occupational group with a high baseline risk. Other ‘essential’ occupational groups are experiencing unprecedented changes in their working environments that may affect their physical and mental health as well as their labour market attachment.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Healthcare workers are a particularly vulnerable group due to their higher risk of being infected by SARS-CoV-2 and their working conditions during the height of infections included long work hours, cancelled holidays, adverse physical and psychosocial work conditions, that is, high psychological and emotional demands and low control. 18 19 These working conditions, together with moral distress in relation to the family situation, may increase the risk for mental health problems and sickness absence in this female-dominated occupational group with a high baseline risk. Other ‘essential’ occupational groups are experiencing unprecedented changes in their working environments that may affect their physical and mental health as well as their labour market attachment.…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Public health workers who were unable to take time off from work when they needed were nearly twice as likely to report symptoms of an adverse mental health condition (prevalence ratio range = 1.84-1.93) as were those who could take time off. Among those not able to take time off from work (8,586), the most common reasons were concern about falling behind on work (64.4%), no work coverage (60.6%), and feeling guilty (59.0%); 18.2% reported that their employer did not allow time off from work. Needing mental health counseling/services in the last 4 weeks, but not receiving these services, was reported by nearly one in five (19.6%) respondents.…”
mentioning
confidence: 99%
“…This prevented examination of psychosocial occupational stressors and lifestyle factors such as physical activity, body weight, smoking, and alcohol intake, which have previously been identified as important prognostic factors of sickness absence in non-clinical populations. 15,22,65 Similarly, data quality issues provide an alternative explanation for that certain features were not selected in the final model. This included noise owing to missingness between 20 to 30% in some chronic pain experience questionnaires and misclassification in employment status.…”
Section: Discussionmentioning
confidence: 99%